Analysis of Conversations in Gen Z WhatsApp Groups: Language Style, Emojis, and Pragmatic Meaning - Samsidar, Samsidar (Journal of Linguistica, 2025)
This study aims to analyze the dynamics of language style, emoji usage, and pragmatic meaning in Gen Z WhatsApp conversations through a Systematic Literature Review (SLR) approach. This study identifies how these linguistic and nonverbal elements function to build intimacy, solidarity, creativity, and digital identity. The research method involved collecting 26 reputable articles (2020–2025) from international and national databases. The data were analyzed through reduction, categorization, thematic synthesis, and pragmatic interpretation. The results show that language styles such as slang, acronyms, interjections, and phonological games serve to strengthen social closeness and create informal communication spaces for Gen Z. Emojis are used in multiple ways, both as emotional expressions, phatic markers, conflict mitigation, and tools to clarify the context of messages. The pragmatic meanings that emerge tend to be fluid, flexible, and often involve maxim violations, especially relevance, but this actually strengthens group identity. Synthesis tables and graphs show that phatic functions and identity construction are the most dominant elements in Gen Z's WhatsApp communication. The research conclusion confirms that Gen Z conversations are a complex pragmatic ecosystem, highly contextual, and constantly evolving in line with the dynamics of digital culture.